Question

Find the general solution of the ODE:

x^{2}(y′)^{2} + yy′(2x+y) + y^{2}= 0

Answer #1

Since the solution technique is not mentioned analytic/numerical. I am giving a numerical solution using MATHEMATICA. If you are not convinced with the solution you can ignore the solution and no need to consider this problem for payment.

DSolve[x^2*(y'[x])^2 + y[x]*y'[x]*(2*x + y[x]) + (y[x])^2 == 0, y[x], x]

This produces the solution

That is first solution is

and the second solution is

find the general solution to the ODE: y''+yx^2 =0

find the general solution of following ”AIRY” ODE
y’’+6y=0

Find the general solution to the ODE y2
-10y+21=dy/dx

dy/dx = 2 sqrt(y/x) + y/x (x<0)
Find general solution of the given ODE

Find the Second Derivative
d2ydx2
when y is given by:
x2+y2-2x+4y-20=0

Verify that the equation y = x2+ 2x+2+Cex
is a solution to the differential equation
y'-y+x2=0.

2xy/x2+1−2x+(ln(x2+1)−2)y′=0 ODE method of
exactness
y(5)+12y(4)+104y(3)+408y′′+1156y′=0
constant coefficient
y′′−4y′−12y=xe4x Underdetermined Coeffecient

The general solution of the equation
y′′+6y′+13y=0 is
y=c1e-3xcos(2x)+c2e−3xsin(2x)
Find values of c1 and c2 so that y(0)=1
and y′(0)=−9.
c1=?
c2=?
Plug these values into the general solution to obtain
the unique solution.
y=?

Find the minimum value of the function f(x,y)=2x+y, subject to
the constraint x2+y2=5.

Solve the initial-value problem. y"-6y'+9y=0; y(0)=2,
y'(0)=3
Given that y1=x2 is a solution to y"+(1/x)
y'-(4/x2) y=0, find a second, linearly independent
solution y2.
Find the Laplace transform. L{t2 *
tet}
Thanks for solving!

ADVERTISEMENT

Get Answers For Free

Most questions answered within 1 hours.

ADVERTISEMENT

asked 27 minutes ago

asked 27 minutes ago

asked 36 minutes ago

asked 57 minutes ago

asked 1 hour ago

asked 1 hour ago

asked 1 hour ago

asked 1 hour ago

asked 1 hour ago

asked 1 hour ago

asked 2 hours ago

asked 2 hours ago